SHARIA BANKING FINANCING FOR MICRO BUSINESS DEVELOPMENT WITH MUSYARAKAH MUTANAQISAH CONTRACTS - Nurmalika, Shintya Putri Ayu; Irkhami, Nafis (Journal of Sharia Economics, 2026)
Islamic banking plays a strategic role in expanding access to financing for micro and small enterprises through partnership-based financial instruments. One scheme with strong potential for this purpose is the musyarakah mutanaqisah contract, a diminishing partnership arrangement in which ownership shares are gradually transferred from one party to another over time. This study examines the role of musyarakah mutanaqisah in small business financing, its implementation mechanisms within Islamic banking institutions, and the challenges encountered in its application.This research employs a qualitative approach using descriptive-analytical methods based on a literature review of Islamic finance studies, regulatory frameworks, DSN–MUI fatwas, and publications from Islamic financial institutions. The findings indicate that musyarakah mutanaqisah provides an alternative financing mechanism that strengthens access to capital for small enterprises through partnership-based financing, proportional risk sharing, and more equitable asset ownership structures. However, its implementation remains constrained by limited public literacy, the complexity of contractual structures, and practices that do not always fully reflect genuine profit-sharing principles. This study contributes to the literature by positioning musyarakah mutanaqisah as a productive asset financing instrument for small enterprises within the framework of maqashid al-shariah. Future research should explore its empirical application in Islamic microfinance institutions to assess its effectiveness in promoting inclusive economic development.